The alteration of chondrules and matrices in new Antarctic carbonaceous chondrites - Kojima, Hideyasu; Ikeda, Yukio; Yanai, Keizo (1984)
P(論文) Seven carbonaceous chondrites, Yamato-791717 (CO3), -74135 (CO3), -793321 (CM), -791198 (CM), -790003 (CM), Belgica-7904 (CM) and Y-791824 (CM) have been studied petrographically and petrologically to characterize their state of alteration. The degree of alteration of these specimens varies widely, from unaltered Y-791717 to intensely altered Y-791824. Petrographical criteria and chemical compositions, especially the Si-Mg-Fe ratios of chondrules and matrices, can be used to define the degree of alteration of CM chondrites. The degree of alteration is classified into four stages, as follows : (1) Unaltered stage, (2) Weakly-altered stage, (3) Moderately altered stage and (4) Intensely altered stage. No CM chondrite belonging to stage 1 has been found. Y-793321 and -791198 are altered to stage 2. Y-790003 belongs to stage 3,and the alteration degree of Y-791824 lies between stage 3 and 4. B-7904 appears to have suffered thermal metamorphism after being intensely altered. departmental bulletin paper